Factors influencing childbirth fear among Asian women: a scoping review - Kalok, Aida; Kamisan Atan, Ixora; Sharip, Shalisah; Safian, Nazarudin; Shah, Shamsul Azhar (Frontiers in Public Health, 2025)
Fear of childbirth (FOC) or tokophobia adversely affects women during pregnancy, delivery, and postpartum. Childbirth fear may differ across regions and cultures. We aimed to identify factors influencing the fear of childbirth among the Asian population. A systematic literature search was performed using the PubMed, Scopus, and Web of Science databases in November 2023. Original articles in English with research conducted in Asian countries were included. The independent factors associated with childbirth fear, from the relevant studies were identified and discussed. Forty-six papers met the eligibility criteria but only 26 studies were discussed in this review. The significant factors were categorized into (1) demographics, (2) clinical, (3) healthcare service, (4) childbirth education & information, and (5) COVID-19 pandemic. The prevalence of childbirth fear among Asians ranged between 56.6 and 84.8%. Significant demographic factors included age, education, marital status, economic status, and area of residence. Greater levels of tokophobia were linked to nulliparity, unplanned pregnancy, infertility, miscarriage, and pregnancies at risk. Effective doctor-patient communication and more frequent antenatal visits were shown to alleviate maternal childbirth fear. There was consistent evidence of prenatal childbirth education’s benefit in reducing FOC. The usage of smartphone apps and prolonged exposure to electronic devices were linked to a higher degree of tokophobia. Nulliparas who received too much pregnancy-related information also reported increased childbirth fear. There was a positive correlation between maternal fear of COVID-19 infection and FOC. Keeping updated with COVID-19 information increased the maternal childbirth fear by two-fold. In conclusion, a stable economy and relationship contribute to lesser childbirth fear among Asian women. Poor maternal health and pregnancy complications were positive predictors of FOC. Health practitioners may reduce maternal childbirth through women’s education, clear communication as well as accurate information and guidance to expectant mothers. Further study is required into the content of childbirth fear among Asian women. These research findings hopefully will lead to the development of culturally adapted screening tools and interventions that reduce the burden of FOC among expectant mothers.